Environmental refugees in developing nations: exploring the causes and impact - Redelinghuys, Nola; Pelser, Andre (University of the Free State, 2000)
The phenomenon of environmental refugees is a little recognised and largely undefined migration trend that is expected to show dramatic acceleration in the near future as environmental degradation renders large areas uninhabitable. This article explores the phenomenon, arguing that current conceptualisations concerning migration are too narrow to deal adequately with this type of forced migration. A re-assessment of current categorisations and policy frameworks - concerning forced migration in general, and forced environmental migration in particular - is therefore necessary. Furthermore, the social factors fueling environmental degradacion, which in its turn leads to environmental refugee movements, are discussed. Attention is also paid co the impact chat these forced migrants may have on host countries.

Omgewingsvlugtelinge is 'n grootliks ongedefinieerde verskynsel wat nie genoegsame erkenning geniet nie, alhoewel hierdie tipe migrasie ongekend sal toeneem soos omgewingsverval in die toekoms groot areas onbewoonbaar maak. Hierdie artikel ondersoek die verskynsel van omgewingsvlugtelinge. Daar word geredeneer dat huidige konseptualiserings te eng is om hierdie vorm van gedwonge migrasie bevredigend te hanteer. 'n Herevaluering van huidige kategoriserings en beleidsraarnwerke - gedwonge migrasie in die algemeen, en gedwonge omgewingsmigrasie in besonder - is derhalwe noodsaaklik. Verder word die sosiale faktore wat omgewingsagteruitgang bevorder, en gevolglike omgewingsvlugtelingbewegings ontketen, bespreek. Aandag word ook gegee aan die impak wat hierdie gedwonge migrasie op gasheerlande het.